A chromomeric model for nuclear and chromosome structure. - Cook, P (1995)
The basic structural elements of chromatin and chromosomes are reviewed. Then a model involving only three architectural motifs, nucleosomes, chromatin loops and transcription factories/chromomeres, is presented. Loops are tied through transcription factors and RNA polymerases to factories during interphase and to the remnants of those factories, chromomeres, during mitosis. On entry into mitosis, increased adhesiveness between nucleosomes and between factories drives a 'sticky-end' aggregation to the most compact and stable structure, a cylinder of nucleosomes around an axial chromomeric core.